Addition of glycerol enhances the flexibility of gelatin hydrogel sheets; application for in utero tissue engineering. Issue 6 (9th November 2020) - Watanabe, Miho; Li, Haiying; Yamamoto, Masaya; Horinaka, Jun‐ichi; Tabata, Yasuhiko; Flake, Alan W
Abstract: Gelatin hydrogels are naturally derived scaffolds useful for tissue engineering because of their cytocompatibility and controllable degradability. However, they are brittle and inflexible when dry, which limits their use for in utero tissue engineering in large animal models. Therefore, in this study, we attempted to generate flexible gelatin sheets by adding various plasticizers with different molecular weights (MW). We systematically evaluated the flexibility, sustainability, and potential clinical utility of the resulting flexible gelatin sheets. Gelatin sheets with low‐MW plasticizers, such as monosaccharides or sugar alcohols, showed a reduced tensile modulus in dynamic viscoelasticity, which reflected their actual flexibility. Wet gelatin sheets containing plasticizers showed higher tensile strength than the nonplasticizer control, although wet gelatin sheets under all conditions had a much lower tensile strength than dry gelatin sheets. In a functional study, gelatin sheets containing glycerol, which has the lowest MW among sugar alcohols, showed encouraging results, such as good fit to the curvature of the experimental animal, biocompatibility, and suitability for endoscopic approaches. The findings of this study should enable the expansion of future applications for flexible gelatin sheets.